Industrial Marketing - Moore, James R.; Southern Illinois Univ., Carbondale. Dept. of Vocational Education Studies (Delhi: PHI, 2010)
This report presents a brief description of a project to develop materials toward a competency-based Industrial Marketing curriculum guide as well as materials developed by the project. The narrative section explains how two of three project objectives were accomplished: (1) identify entry positions and career ladders in the industrial marketing area which will be used by secondary, postsecondary, and adult educators in teaching and by trainers in business/industry and (2) identify and validate employment competencies. (Objective 3, to categorize and develop instructional objectives, was not accomplished.) The appendixes present all materials developed. Appendixes A and B provide the career ladders and job descriptions for three occupations: full-function wholesaling, limited-function wholesaling, and functional middlemen. The preliminary and revised validation instruments developed for use in the validation of the employment competencies are found in appendixes C and D. (YLB)
Sponsoring Agency: Illinois State Office of Education, Springfield. Div. of Adult Vocational and Technical Education.
Contract Number: R-33-11-D-0542-448.
ERIC Note: Pages 4-22 were removed to preserve confidentiality of personal information.
Microfiche.
Keywords: Adult Education; Career Ladders; Competency Based Education; Curriculum Development; Curriculum Guides; Distributive Education; Entry Workers; Industrial Education; Job Skills; Job Training; Marketing; Material Development; Merchants; Postsecondary Education; Secondary Education; Validity; Wholesaling; Industrial Marketing; Guides, Non-Classroom.; Reports, Descriptive